Using water with different levels of salinity by paddy fields: a Brazilian case study. Issue 22 (15th December 2020) - Denardin, Luiz Gustavo de Oliveira; Carmona, Felipe de C.; Alves, Lucas A.; Flores, João Pedro M.; Weber, Eliseu J.; Martins, Amanda P.; Tiecher, Tales; Anghinoni, Ibanor
ABSTRACT: On the coastal plain of Rio Grande do Sul State, Brazil, the soil salinity is strictly related to the quality of irrigation water sources connected to the Atlantic Ocean, especially the Patos Lagune. The possibility of using this water source for irrigation of rice fields depends on the salinity level of the water and soil, which can be estimated knowing the sodium (Na + ) content of both. This study aimed to establish a relationship between the electrical conductivity (EC) and Na + content of the water of the Patos Lagune and to determine the possibility of water use for flooded rice, with increasing levels of EC, on the Brazilian coastal plain. Water samples were collected at different points in the Patos Lagune to determine the levels of Na + and EC. The equation determined was as follows: Na (mg L −1 ) = 179.61 * EC – 183.25. The possibility of using irrigation water was different between the sites. Most soils can receive the total volume of water demanded by flooded rice since the water EC does not exceed 1.0 dS m −1 . With an EC of 1.5 dS m −1, an alternative irrigation water source should be obtained.